Arguing Using Critical Thinking - Marteney, Jim (Open textbook library., 2020)
There is a quote that has been passed down many years and is most recently accounted to P.T. Barnum, “There is a sucker born every minute.” Are you that sucker? If you were, would you like to be “reborn?” The goal of this book is to help you through that “birthing” process. Critical thinking and standing up for your ideas and making decisions are important in both your personal and professional life. How good are we at making the decision to marry? According to the Centers for Disease Control, there is one divorce in America every 36 seconds. That is nearly 2,400 every day. And professionally, the Wall Street Journal predicts the average person will have 7 careers in their lifetime. Critical thinking skills are crucial. Critical thinking is a series learned skills. In each chapter of this book you will find a variety of skills that will help you improve your thinking and argumentative ability. As you improve, you will grow into a more confident person being more in charge of your world and the decisions you make.